The Well-Being of Workers and Teachers Analysis in the Midst of COVID-19 Pandemic to Achieve Work-Life Balance - Muhammad Thoha; Hari Susanta Nugraha; Sri Suryoko; Nelly Rhosyida; Tuti’ Nadhifah (Khazanah Sosial, 2022)
The COVID-19 pandemic has disrupted human activity throughout the world. This disruption is also supported by the advancement of technology, particularly in the field of information and communication. However, significant change may cause negative effect for the well-being of many people, which could lead to the imbalance of work-life. With the concept of well-being that divided into four components, personal resources, organizational management, functioning at work, and experience at work, also the concept of work-life balance from the perspective of conflict theory and enrichment theory, this research will examine the well-being of workers and teachers and how it affected their work-life balance amidst pandemic. The study uses qualitative content analysis, the research findings include: (1) the negativity and positivity caused by the pandemic towards the well-being of workers and teachers, (2) and how to achieve work-life balance amidst pandemic from the conflict theory perspective and enrichment theory perspective.